Module of Server Administration in Networks with 4D Models - Wirawan Putrayadi (Universitas Negeri Malang, 2014)
Modul Administrasi Server dalam Jaringan dengan Model 4D Abstrak: The aims of this study are: (1) to produce the administration server module in Network (2) to know the properness levels of the used module. The development of the module is adopting the 4D models by Thiagrajan et al. The 4D models have development steps which are: define, design, develop, dan disseminate. The Assessment of the module is validated based on content expert and learning media, which is tested individually and group (limited). The resulted module are provided with relevant pictures or illustration in field, job sheet that able to give activities to the student to improve student activeness, in practice, the only needs is laptop/computer, also the module can be used individually or in group, outside schools, learning speed is based on the individuals and teachers act as facilitator. Based on the expert of the material, it shows  that the properness of the module is 78%, from the expert of the learning media is 81%, meanwhile the individual test shows 77% and from group (limited) shows 80%. Key Word: module, 4d model, server Abstrak: Tujuan penelitian pengembangan ini adalah: (1) menghasilkan modul administrasi server dalam jaringan; (2) mengetahui tingkat kelayakan modul untuk digunakan. Pengembangan modul mengadopsi model 4-D dari Thiagarajan dkk. Model 4-D memiliki tahapan pengembangan meliputi:  define, design, develop, dan disseminate. Penilaian modul divalidasi berdasarkan ahli isi dan media pembelajaran, kemudian diujicobakan secara perorangan dan kelompok terbatas. Hasil produk modul yang dikembangkan dilengkapi dengan gambar-gambar atau ilustrasi yang relevan dengan kenyataan di lapangan, jobsheet yang dapat memberikan kegiatan praktik agar siswa lebih aktif, dalam kegiatan praktik hanya diperlukan komputer/laptop, serta modul dapat digunakan secara mandiri maupun ber-kelompok, di luar sekolah, belajar sesuai dengan kecepatan masing-masing, dan guru bertindak se-bagai fasilitator. Penilaian modul oleh beberapa ahli materi menunjukkan kelayakan sebesar 78%, ahli media pembelajaran sebesar 81%, sedangkan penilaian hasil uji coba perorangan sebesar 77% dan penilaian dari hasil uji coba kelompok terbatas sebesar 80%.   Kata kunci: modul, model 4-D, server